Hubungan antara Kemandirian Emosi Dengan Motivasi Belajar Peserta Didik di MT.s Muhammadiyah Wuring - Rahman, Syafir (Lembaga Riset Mutiara Akbar, 2022)
The purpose of this study is to find out the relationship between emotional independence and the learning motivation of Mts Muhammadiyah Wuring learners. This research was conducted at Mts Muhammadiyah Wuring. The population of this study was 54 students. A sample of 40 students. The instrument consists of a kuisoner. To find out the validation of this study, researchers used the formula Person Prodact Moment through the SPSS v. 23 for window program. To find out quantitative descriptive correlations use data analysis techniques. After the data is distributed. From the data of the study analysis showed that the value of the correlation coefficient of 0.886 with a positive sign and obtained the value p = 0.000 so that from both variables obtained significant values both at the level of 0.05 and can be seen from the correlation coefficient number. With demikain the value can be compared with rtabel in the study which is at a significant level of 5% for a sample of 40 so that the number 0.3044 is obtained and it is seen that rhitung > rtabel or 0.886 > 0.3044, so that the null hypothesis (H0) is obtained in reject and Hypothesis (H1) is accepted. This means that there is a positive and significant relationship of emotional independence with the learning motivation of MTs. Muhammadiyah Wuring learners.